Phule Kiran (SSF 16-02): A new spiny and high yield Safflower variety for rainfed and irrigated conditions of the country: Phule Kiran (SSF 16-02): A new spiny and high yield Safflower variety for rainfed and irrigated conditions of the country - A B RAJGURU; L N TAGAD; D R MURUMKAR; S I TAMBE; S K SHINDE (Journal of Oilseeds Research, 2023)
A Safflower variety Phule Kiran (SSF 16-02) derived through the pedigree selection method from a germplasm GMU-2757 was evaluated in station trial for yield during 2015-16 and tested in University multilocation varietal trial during 2016-17, simultaneously; it was evaluated in All India Coordinated Varietal Trial from 2017-18, 2018-19, and 2019-20. Based on the performance in station, university multilocation varietal trial, and coordinated trials, Phule kiran (SSF 16-02) recorded 9.84 % and 17.47 higher yield over the check A1 and PBNS 12 respectively. Also SSF 16-02 recorded 14.98 % and 18.67 % higher oil yield over the checks A1 and PBNS 12 respectively. It was responsive to higher doses of fertiliser and late sown conditions. The variety Phule kiran (SSF 16-02) was identified in Annual Group Meeting held at IIOR, Hyderabad during 13-14th August 2020 for rainfed and irrigated safflower growing areas of the country (Maharashtra, Karnataka, Madhya Pradesh, Chhatisgad and Telegana state).